Abstract Number ‐ 120: Using Gadolinium‐based Contrast in Middle Meningeal Artery Embolization: A Case Series - Cleo Zarina A Reyes; Srihari Sundararajan; Darryn Shaff (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Nonacute subdural hematoma (SDH) is a common pathology, particularly in the elderly population, affecting 74 persons per 100 000 aged >65 years old. Though surgical evaluation is the current golden standard treatment for symptomatic NASDH, there has been a paradigm shift towards middle meningeal artery embolization (MMAe), which is less invasive and addresses the underlying pathophysiology. MMAe traditionally uses iodine‐based contrast angiography to assess the anatomy and other branches relative to the distribution of the SDH. Due to the abrupt shortage of intravenous iodine‐based contrast secondary to COVID19 pandemic and consequent April 1,2022 lockdown in Shanghai manufacturers (GE Healthcare), we report three successful cases of MMAe utilizing gadolinium‐based contrast angiography. Methods Informed consent that an alternative contrast medium was obtained from the patients. All procedures were done under general anesthesia, see methods below. All patients tolerated the procedures well, without any nausea, urticaria, angioedema, or bronchospasm. On 6–8 weeks outpatient follow‐up and repeat imaging, all patients have near resolution or improvement of SDH size and no lasting post‐procedural complications were reported. Results Case 1: A 50‐year‐old man with history of traumatic SDH (5 months prior) presented with 5 days history of dysarthria and lethargy. Computed tomography head (CTH) revealed non‐acute bilateral subdural hemorrhage with 6 mm left‐to‐right midline shift. Patient then underwent burr hole evacuation of left‐sided subdural hematoma, and subsequently underwent prophylactic left MMAe and upfront right MMAe. With a transradial approach, 41 cc of gadoteridol contrast (ProHANCE) was used for angiography. No significant ophthalmic artery anastomosis was observed. PVA particles measuring 150–250 microns were then injected until there was significant stasis of forward flow and reflux around the catheter tip. Case 2: A 49‐year‐old man with history of traumatic SDH (6 months prior) presented with 1 month history of headaches, word‐difficulty finding and right sided clumsiness. CTH revealed 2.3 cm mixed density left SDH with a 1.6 mm left‐to‐right midline shift. Patient underwent left frontotemporoparietal craniotomy and subdural hematoma evacuation. 3 days later, patient underwent prophylactic left MMAe using a transfemoral approach with 6.1 cc of gadoterate meglumine (Dotarem) contrast for angiography. No definite external‐to‐internal dangerous collateral pathways were noted and no ocular supply was seen. Liquid embolization proceeded utilizing Onyx 34 with penetration into mid‐level meningeal branches. Case 3: A 55‐year‐old woman presented with 2‐week history of headaches and blurry vision. CTH showed a large 2.2 cm left mixed density SDH with 9.6 mm left‐to‐right midline shift. Patient underwent burr hole evacuation of left‐sided subdural hematoma and subsequent left prophylactic MMAe. With a transfemoral approach, 6.7 cc of gadoteridol contrast (ProHANCE) was used for angiography. No obvious external to internal dangerous collateral pathways were noted. The balloon catheter was advanced just proximal to the bifurcation and liquid embolization with Onyx 34 was achieved. The middle meningeal artery demonstrated complete occlusion proximal to the bifurcation. Conclusions This case series suggests that utilizing a gadolinium‐based contrast for angiography to guide MMA embolization is feasible, effective in visualization of dangerous external‐to‐internal anastomoses (including the ophthalmic artery), and safe for patients.